Штучний інтелект як фактор конвергенції праці та капіталу: потенціал використання для розвитку економіки України - Kuranda, Maksym V.; Bogutska, Olga A. (Institute of Industrial Economics of NAS of Ukraine, 2025)
The reduction of human resources and population aging due to the second demographic transition is a pressing global issue, the resolution of which will determine the future of humanity in the long term. In Ukraine, this problem is significantly exacerbated by the consequences of war: combat losses, severe injuries, and population migration have substantially decreased human resources. The main challenge in the post-war reconstruction of Ukraine will be a severe demographic crisis and a shortage of skilled labor.This issue can be addressed by increasing productivity per capita through the implementation of modern automation technologies capable of compensating for the scarcity of human capital with machine capital. This capital integrates artificial intelligence and automated technologies and is characterized by unlimited reproducibility. Unlike traditional capital, which primarily acts as a tool requiring human labor, artificial intelligence operates autonomously, enabling the scaling of the economy even under conditions of stagnation or a decline in human capital. Although in the short term the rapid implementation of automation may increase social tensions, in the long term the automation of routine processes creates conditions for human potential development and encourages the acquisition of skills necessary for high-skilled labor.The purpose of this article is to determine the potential of using artificial intelligence as a convergence factor of labor and capital for the development of Ukraine's economy under the conditions of a declining workforce.The article attempts to consider artificial intelligence as a tool to address the issue of human resource reduction. It is established that artificial intelligence can stimulate economic growth by replacing labor, which is a limited resource, with capital, which has the potential for unlimited reproduction. The impact of artificial intelligence technologies on the labor market is analyzed. Relevant directions for integrating innovative technologies into key economic sectors are identified, and the specific features of the national economy affecting AI integration capabilities are examined. The article proposes solutions to the problem of human resource shortages and the lack of skilled workers through the automation of certain economic sectors and the introduction of retraining programs for workers. The language of the article is Ukrainian.